The organization of business interests: Studying the associative action of business in advanced industrial societies - Philippe C. Schmitter; Wolfgang Streeck (Max-Planck-Institut für Gesellschaftsforschung, 1999)
The paper presents a theoretical outline for a cross-national comparative study of business associations. It identifies two clusters of independent variables that are assumed to affect the structure of intermediary organizations: properties of the represented group (Logic of Membership) and properties of the state and other political institutions such as trade unions (Logic of Influence). It goes on to develop a model of the organizational properties of business associations as they respond to these two logics and to other functional exigencies (Logic of Goal Formation and Logic of Effective Implementation). In a further step, the paper suggests four dimensions (Domains, Structures, Resources, Outputs) in which the organizational development of interest associations from lower to higher levels of organizational complexity and strategic autonomy can be studied. – – Das Papier enthält einen theoretischen Entwurf für eine international vergleichende Studie von Wirtschaftsverbänden. Es benennt zwei Gruppen von unabhängigen Variablen, die die Struktur von intermediären Organisationen beeinflussen: Eigenschaften der vertretenen Gruppen (Mitglieder-Logik) und Eigenschaften des Staates und anderer politischer Institutionen wie der Gewerkschaften (Einfluß-Logik). Im Anschluß daran wird ein Modell der organisatorischen Eigenschaften von Interessenverbänden als Ausdruck der Einwirkung der beiden genannten Logiken sowie anderer funktionaler Zwänge (Logik der Zielformierung, Logik der effektiven Zielverwirklichung) entwickelt. Danach werden vier organisatorische Dimensionen vorgeschlagen (Domänen, Strukturen, Ressourcen, Tätigkeiten), in denen die organisatorische Entwicklung von Interessenverbänden von niedrigeren zu höheren Niveaus organisierter Komplexität und strategischer Autonomie untersucht werden kann.
Keywords: 300